Do Shade-Grown Coffee Plantations Pose a Disease Risk for Wild Birds? - Hernández, Sonia M. (2013)
Shade-grown coffee plantations are often promoted as a conservation strategy for wild birds. However, these agro-ecosystems are actively managed for food production, which may alter bird behaviors or interactions that could change bird health, compared to natural forest. To examine whether there is a difference between the health parameters of wild birds inhabiting shade-grown coffee plantations and natural forest, we evaluated birds in Costa Rica for (1) their general body condition, (2) antibodies to pathogens, (paramyxovirus and Mycoplasma spp.), and (3) the prevalence and diversity of endo-, ecto-, and hemoparasites. We measured exposure to Mycoplasma spp. and para- myxovirus because these are pathogens that could have been introduced with domestic poultry, one mechanism by which these landscapes could be detrimental to wild birds. We captured 1,561 birds representing 75 species. Although seasonal factors influenced body condition, we did not find bird general body condition to be different. A total of 556 birds of 31 species were tested for antibodies against paramyxovirus-1. Of these, five birds tested positive, four of which were from shade coffee. Out of 461 other tests for pathogens (for antibodies and nucleotide detection), none were positive. Pterolichus obtusus, the feather mite of chickens, was found on 15 birds representing two species and all were from shade-coffee plantations. Larvated eggs of Syngamus trachea, a nematode typically associated with chickens, were found in four birds captured in shade coffee and one captured in forest. For hemoparasites, a total of 1,121 blood smears from 68 bird species were examined, and only one species showed a higher prevalence of infection in shade coffee. Our results indicate that shade-coffee plantations do not pose a significant health risk to forest birds, but at least two groups of pathogens may deserve further attention: Haemoproteus spp. and the diversity and identity of endoparasites.